Impact of digital transformation on the competitive advantage of companies - Zimonjić Marijana (Megatrend Revija)
The introduction of digital transformation has influenced the competitive advantage of companies. Key factors of digital transformation, as well as ways in which technologies such as artificial intelligence, big data, automation, and cloud computing enable companies to improve their operations, innovate products and services, and achieve sustainable competitive advantage in the market. The research aims to provide a comprehensive overview of the impact of digital transformation on competitive advantage, identify success factors, as well as the challenges companies face. The research findings will help managers and business leaders to better understand how they can leverage digital technologies to achieve sustainable growth and competitive advantage in the modern marketplace. The issue of digital business transformation has become a subject of interest for management theorists and practitioners only in recent years, so there is a lack of theoretical contributions in this area. The ultimate goal of digital business transformation is to create added business values. Organizations can make this goal more achievable by defining a clear, comprehensive digital transformation strategy that should highlight key digital advantages.